A data set from flash X-ray imaging of carboxysomes - Hantke, M. F.; Hasse, D.; Ekeberg, T.; John, K.; Svenda, M.; Loh, D.; Martin, A. V.; Timneanu, N.; Larsson, D. S. D.; Van Der Schot, G.; Carlsson, G. H.; Ingelman, M.; et al. (My University, 2016)
Ultra-intense femtosecond X-ray pulses from X-ray lasers permit structural studies on single particles and biomolecules without crystals. We present a large data set on inherently heterogeneous, polyhedral carboxysome particles. Carboxysomes are cell organelles that vary in size and facilitate up to 40% of Earth's carbon fixation by cyanobacteria and certain proteobacteria. Variation in size hinders crystallization. Carboxysomes appear icosahedral in the electron microscope. A protein shell encapsulates a large number of Rubisco molecules in paracrystalline arrays inside the organelle. We used carboxysomes with a mean diameter of 115±26 nm from Halothiobacillus neapolitanus. A new aerosol sample-injector allowed us to record 70,000 low-noise diffraction patterns in 12 min. Every diffraction pattern is a unique structure measurement and high-throughput imaging allows sampling the space of structural variability. The different structures can be separated and phased directly from the diffraction data and open a way for accurate, high-throughput studies on structures and structural heterogeneity in biology and elsewhere.
Citation: Hantke, M. F., Hasse, D., Ekeberg, T., John, K., Svenda, M., Loh, D., . . . Maia, F. R. N. C. (2016). A data set from flash X-ray imaging of carboxysomes. Scientific Data, 3. doi:10.1038/sdata.2016.61